Performance comparison of organic Rankine cycle with expansion from superheated zone or two-phase zone based on temperature utilization rate of heat source. (15th April 2018) - Sun, Hongchuang; Qin, Jiang; Hung, Tzu-Chen; Lin, Chih-Hung; Lin, Yi-Fan
Abstract: The temperature utilization rate of heat source is defined to evaluate the energy utilization rate of organic Rankine cycles (ORCs). Rotary vane pump, plate heat exchangers and scroll expander are adopted to compare the performance of ORCs with expansion from superheated zone or two-phase zone. The results show that temperature utilization rate increases with the increase of mass flow rate of working fluid and the decrease of mass flow rate of heat source. The working conditions are classified into three types of A, B and C according to starting zone of expansion. The temperature utilization rate keeps almost unchanged for types B and C, but the net electric power output efficiency decreases obviously with the increase of working fluid mass flow. The maximum thermal efficiency, net electric power output efficiency and isentropic efficiency of expander are obtained as 6.1%, 3.01% and 83.5%, respectively. The maximum temperature utilization rate can reach 64.4% with the decrease of heat source mass flow. Furthermore, the rotary van pump is suitable for small-scale ORC with stable volume flow rate, relative high efficiency, good sealing condition and long service life. The highest isentropic efficiency and electricity consumption efficiency of pump are 46.1% and 39.8%, respectively. Highlights: Performances are compared for expansion from superheated zone or two-phase zone. The maximum temperature utilization rate of heat source is 64.4%. The highest isentropic efficiency of pump and expander are 46.1% and 83.5%. The maximum thermal efficiency and net power output efficiency are 6.1% and 3.03%. Rotary vane pump is better than gear pump, plunger pump and centrifugal pump.